Microleakage of high viscosity glass-ionomer and glass-carbomer with and without coating before and after hydrothermal aging - Patır Münevveroğlu, Asli; Ozsoy, Alev; ballı akgol, beyza; bozatlioglu, ruhan; korkut, pelin; uysal, busra; Ozcan, Mutlu (Brazilian Dental Science, 2019)
Objective: The objective of this study was to evaluate the microleakage patterns of GIC and GGC with and without their protective surface coatings on enamel and dentin margins before and after aging. Material and Methods: Two rectangular cavities (height: 2 mm; width: 3 mm; depth: 1.5 mm) were prepared on each tooth at the cemento-enamel junction were prepared on human permanent molars (N=56) and the teeth were randomly assigned to be restored with one of the following: a) high viscosity glass-ionomer cement (GIC) (EQUIA Fil, C Corp., Tokyo, Japan) (n=28), b) glass-carbomer cement (GCC) (Glass Carbomer Products, Leiden, The Netherlands) (n=28). Half of the teeth were further divided into two groups where one group received protective surface coating (SC) (G-Coat Plus, GC Corp) (n=14) and the other group did not (n=14). Half of the teeth were stored for 24 hours (n=7), and the other half was thermocycled (5000 cycles, 5-55°C) (n=7). For microleakage analysis, the teeth were immersed in 5% methylene blue dye for 24 hours, sectioned into two equal halves. Microleakage patterns were evaluated using stereomicroscope and scored on a scale of 0-3 (0: No dye penetration, 1: Dye penetration less than half of the axial wall, 2: Dye penetration more than half the axial wall, 3: Dye penetration spreading along the axial wall). Data were analyzed using Kruskal-Wallis tests at the significance level of 0.05. Results: Compared to 24 h storage, after thermocycling, surface coating on GIC decreased microleakage significantly compared to GCC (p=0.046) but not for GCC. In the thermocycled groups, coated GIC showed significantly less leakage at the enamel margin but no significant difference was found with both GIC and GCC in the dentin margins. Conclusion: The application of surface coating significantly reduced the microleakage scores of GIC but not GCC, within the enamel margins only.KeywordsGlass-carbomer; Glass-ionomer; Microleakage.